A new fuzzy performance modeling for evaluating the trade-off among robustness, quality and capacity in watermaking algorithms - Emami, Mir Shahriar (2012)
There are several digital watermarking metrics proposed by researchers. These metrics can determine the robustness and the imperceptibility of watermarking schemes discretely. Here, there is a lack of an effective strategy to evaluate the balanced trade-off between these requirements. Meanwhile, it is hardly possible to determine crisp thresholds to limit the acceptable and unacceptable boundaries for robustness and imper-ceptibility. Hence, it is difficult to obtain an accurate mathematical model in order to evaluate the degree of trade-off between watermarking requirements. Thus, it is most advantageous to adopt the fuzzy-based model to fulfill this need. This paper develops a fuzzy inference system (FIS) effectively for exploring the performance trade-off among watermarking performance requirements. We implemented this technique to evaluate EISB (Enhanced Intermediate Significant Bit) watermarking scheme. We also focused on different intensities of Reset Removal Attack which were less considered before, by other researchers. Two main contributions of this paper are the performance fuzzy model itself, and the performance analysis of this model which was carried out and confirmed by results via simulation. A new fuzzy performance modeling for evaluating the trade-off among robustness, quality and capacity in watermarking algorithms.